1987
DOI: 10.1210/endo-120-4-1417
|View full text |Cite
|
Sign up to set email alerts
|

Protein Degradation in Skeletal Muscle during Experimental Hyperthyroidism in Rats and the Effect of β-Blocking Agents*

Abstract: beta-Blocking agents are increasingly used in the management of hyperthyroid patients. The effect of this treatment on increased muscle protein breakdown in the hyperthyroid state is not known. In the present study, experimental hyperthyroidism was induced in rats by daily ip injections of T3 (100 micrograms/100 g BW) during a 10-day period. Control animals received corresponding volumes of solvent. In groups of rats the selective beta-1-blocking agent metoprolol or the nonselective beta-blocker propranolol wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…It has been shown in vitro (tyrosine release method) that the global breakdown rate of mixed proteins in diaphragm and hindlimb muscles is increased in young rats infused with T 3 for 4 -10 days in a process regulated through the proteosome pathway (1,33). Although muscle protein breakdown rate cannot be directly measured in vivo, the present study provides indirect support that tissue protein breakdown rate was increased in T 3 -treated rats.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…It has been shown in vitro (tyrosine release method) that the global breakdown rate of mixed proteins in diaphragm and hindlimb muscles is increased in young rats infused with T 3 for 4 -10 days in a process regulated through the proteosome pathway (1,33). Although muscle protein breakdown rate cannot be directly measured in vivo, the present study provides indirect support that tissue protein breakdown rate was increased in T 3 -treated rats.…”
Section: Discussionsupporting
confidence: 51%
“…Most animal studies showed that the mixed protein synthesis rate in skeletal muscle, liver, and heart is stimulated by excess thyroid hormone (1,3,8,9,16,23). In humans, whole body rates of protein synthesis and breakdown are increased in some (20,27,32,35) but not all (19,21) studies of hyperthyroid patients or short-term experimental hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microarray analysis of glucocorticoid-induced myopathy in vivo was described recently (13). Proteolysis is also enhanced in hyperthyroidism (1,4,7), explaining the body weight loss of thyrotoxic patients (20); but in contrast to glucocorticoids, thyroid hormones act as positive regulators of muscle development (9). Microarray analysis of 3,3Ј,5-triiodo-L-thyronine (T 3 )-treated human skeletal muscle confirmed the wide range of T 3 targets (5).…”
mentioning
confidence: 99%
“…In addition, me toprolol treatment also affected growth and food consumption in a way that may indi cate some interference with basal metabolic processes. This apparent increase in energy consumption was somewhat surprising, since p-adrenoceptor-blocking agents are currently used in the treatment of hyperthy roid patients [30], However, recent studies in rats have failed to demonstrate effects of Pi-blockade on some of the metabolic altera- tions induced by triiodothyronine treatment [31,32], It is not possible from the available data to decide neither what the type of dis turbance is underlying the effects of metoprolol on growth and food consumption, nor if the effects were due to the drug itself, or to its metabolite(s) [22,23],…”
Section: Plasma Lipidsmentioning
confidence: 99%